2023
DOI: 10.1002/jhet.4673
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectral characteristics and molecular structure of 2H‐1,3,5‐oxadiazine‐2,4(3H)‐diimine derivatives

Abstract: In this work, we report the synthesis of 2H‐1,3,5‐oxadiazine‐2,4(3H)‐diimine derivatives based on acylated thioureas. The method for the preparation of 1,3,5‐oxadiazine derivatives is based on the reaction of dehydrosulfurization of the starting acylated thioureas under the action of dicyclohexylcarbodiimide (DCC) followed by the [4 + 2] cycloaddition reaction of another DCC molecule to the resulting intermediate carbodiimide. The structure of the obtained derivatives of 1,3,5‐oxadiazine was confirmed by 1H, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The resulting acyl carbodiimide undergoes [4 + 2] Diels-Alder cycloaddition reaction with another molecule of DCC afford 2H-1,3,5-oxadiazine-2,4(3H)diimine derivatives (30a-g). 52 afford desired 2-aminothiazole derivatives (34F1-30) (Scheme 9). 53 Cyclization of pivaloyl thiourea (35) to 5-(tert-butyl)-N-(2,4dichlorophenyl)-1H-1,2,4-triazol-3-amine (36) was carried out by reacting pivaloyl thiourea (35) with hydrazine hydrate in ethanol at room temperature (Scheme 10).…”
Section: Heterocyclization Reactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The resulting acyl carbodiimide undergoes [4 + 2] Diels-Alder cycloaddition reaction with another molecule of DCC afford 2H-1,3,5-oxadiazine-2,4(3H)diimine derivatives (30a-g). 52 afford desired 2-aminothiazole derivatives (34F1-30) (Scheme 9). 53 Cyclization of pivaloyl thiourea (35) to 5-(tert-butyl)-N-(2,4dichlorophenyl)-1H-1,2,4-triazol-3-amine (36) was carried out by reacting pivaloyl thiourea (35) with hydrazine hydrate in ethanol at room temperature (Scheme 10).…”
Section: Heterocyclization Reactionsmentioning
confidence: 99%
“…It was found that the oxadiazine ring in the molecule was at with an accuracy of 0.03 Å (Scheme 8). 52 5-(Tert-butyl)-N-(2,4-dichlorophenyl)-1H-1,2,4-triazol-3amine (36) crystallized in orthorhombic crystal system with Pbca space group. Crystal structure stability of the molecule was due to the presence of intermolecular N-H/N hydrogen bonds and p/p stacking interaction between B rings (Scheme 10).…”
Section: Molecular and Crystal Structurementioning
confidence: 99%
See 2 more Smart Citations